Consumer Tax in Islam and According to Maqashid Syariah - Imam Kamaludin; Dwi Hanif Febriansyah (al-Afkar, Journal For Islamic Studies, 2026)
A country is prohibited from collecting its citizens' assets without a legal basis. Taxes are one of the country's primary products and an essential part of financial policy. Scholars argue, based on ijtihad, that taxes (dharbah) are permissible and arise for reasons that are different from zakat, which is an obligation on the wealth of Muslims. The other side says that no (harmful) tax is permissible or impermissible according to Sharia. Many scholars argue that taxes are prohibited, while others argue that they are permissible. Therefore, we can view tax law, especially in Indonesia, as being based on the maqashid of Sharia. If analyzed from the perspective of two levels of maqashid of Sharia according to As-Syatibi: Al-Daruriyah & Al-Hajjiyyah. Therefore, it can be concluded that consumer tax law is permissible for the benefit and must be obeyed by those who are obliged to pay consumer taxes to avoid undesirable dharuroh.